IMPLEMENTATION OF CRIMINAL DEVELOPMENT IN CORRECTION INSTITUTIONS - Jihan Annisa Mujaddidah; Said Karim; Syamsuddin Muchtar (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This study aims to analyze the implementation of prisoner coaching in Class IIB Polewali Mandar Penitentiary and to analyze the factors that influence the implementation of prisoner coaching in Class IIB Polewali Mandar Penitentiary. This research is empirical research. The data sources used consist of primary data, namely data from informants at Class IIB Polewali Mandar Penitentiary. Secondary data, namely data obtained from books, the internet, and related legislation. Data collection techniques are by interviews and direct observation. All of these data were analyzed by descriptive qualitative. The results of the study show that (1) the implementation of convict coaching in Class IIB Polewali Mandar Penitentiary has been carried out quite well personality development and independence development. Personality development includes fostering religious awareness, fostering awareness of the nation and state, fostering intellectual abilities, fostering legal awareness and skills. While fostering self-sufficiency includes bread making, carpentry, electric welding, hydroponics, barbershop, paving blocks, handicrafts from sticks, laying hens, fisheries, goat farming, sewing, workshops, agriculture, and laundry. (2) The factors that influence the implementation of convict coaching at the Polewali Mandar Class IIB Penitentiary include legal factors, law enforcement factors, facilities or facilities, community factors, and cultural factors, each of which has an interrelated role so that the implementation run optimally.